Cervical cancer screening uptake and associated factors among Women Living with Human Immunodeficiency Virus in public hospitals, eastern Ethiopia - Tesfaye, Dagnachew; Weldegebreal, Fitsum; Ayele, Firayad; Dheresa, Merga (Frontiers in Oncology, 2023)
Background Cervical cancer, the second leading cancer in Ethiopia women, is six times higher among women infected with the Human Immune Virus 1-infected women. Its screening provides protective advantages, and is linked to a decrease in the incidence of invasive cervical cancer and mortality. Although cancer screening has great advantages for early treatment and prevention of further complications, cervical cancer screening uptake is low among women in developing countries. Cervical cancer screening uptake among Women Living with Human Immunodeficiency Virus (WLHIV) is not well known in Eastern Ethiopia. Thus, we aimed to assess cervical cancer screening uptake and its associated factors among WLHIV in public hospitals in Harar, eastern Ethiopia. Methods An institution-based cross-sectional study was carried out on 412 randomly selected HIV-positive women from March 20 to April 20, 2022. The results of the study were presented descriptively in percentages and analytically in odds ratio. Bivariate and multivariable logistic regression analyses were used to determine the presence and degree of association between dependent and independent variables. In the multivariable logistic analysis, a p-value of 0.05, and an adjusted odds ratio with a 95% confidence interval were considered to determine independent predictors for the uptake of cervical cancer screening. Results Cervical cancer screening uptake among WLHIV was 57.5% (95% CI: 52.5, 62.9%). The uptake of cervical cancer screening was significantly associated with age between 20-29 years (AOR = 7.33; 95% CI: 1.98, 27.1), 40-49 years (AOR = 4.37; 95% CI: 1.48, 12.89), tertiary level of education (AOR = 0.197; 95% CI: 0.041, 0.946), good knowledge (AOR = 3.591; 95% CI: 2.123, 6.073), and monthly income of 2501(45.52 ) and above Ethiopian Birr (AOR = 0.389; 95% CI: 0.158, 0.959). Conclusions More than half of the participants had undergone cervical cancer screening. Age, marital status, educational status, monthly income, and awareness of cancer screening uptake were all factors related to cervical cancer screening. To maximize uptake, it is necessary to create specific counseling and education programs that target HIV-positive women.